Kemudahan atau Kapitalisme berkedok Amal? Kajian Netnografi pada Website Amal Kitabisa.com - Moh Rifaldi Akbar (Universitas Bina Sarana Informatika, 2019)
The development of communication technology and the Internet era has led to changes in the donation behavior of the public. According to the Spectator Index 2019, Indonesia as the nation was noted as the most generous nation in the World. Since 2012 the emergence of websites and applications are practicing. The emergence of websites with the aim of crowdfunding raises questions about the charity and practice of capitalism. With all the conveniences provided from mobile-accessible applications, fast internet, mobile banking, apps and websites featuring social issues where the audience can donate and replace the conventional way of donating. On the other hand, crowdfunding-based website such as kitabisa.com impose a 5% percent tax on each charity transaction provided. The ease given in the era of the internet coupled with the presence of the website initiated the way of thinking and new standards in donation practice. Previous studies have not yet fully addressed the cultural backgrounds that underpin a person to make a charity in the era of the internet in which there is a growing of website and internet era. This paper attempts to fill the void by seeing the connection between the Internet era, the website, the behavioral practices and digital captialism with a critical paradigm. This article will search anthropologically by using a netnography method with the goal of digging an audience-based experience through an online-based application or website.